2004
DOI: 10.1212/01.wnl.0000127517.33208.f4
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein in blood and brain from familial Parkinson disease with SNCA locus triplication

Abstract: The authors recently demonstrated that genetic triplication of the SNCA locus causes Parkinson disease. Here it is shown that SNCA triplication results in a doubling in the amount of alpha-synuclein protein in blood. Examination of brain tissue showed a doubling in the level of SNCA message. However, at the protein level in brain, there was a greater effect on deposition of aggregated forms into insoluble fractions than on net expression of soluble alpha-synuclein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
224
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(238 citation statements)
references
References 9 publications
9
224
0
5
Order By: Relevance
“…How alpha synuclein reaches serum from the brain in unknown, but blood levels of alpha synuclein may reflect the gene dosage and/or altered protein expression, since triplication of the alpha synuclein gene causes increased brain expression and a doubling of blood alpha synuclein (Miller et al, 2004). Cocaine abuse leads to state dependent increases in the levels of alpha synuclein in postmortem brain (Mash et al, 2003;Qin et al, 2005) and peripheral blood as shown in this report.…”
Section: Discussionmentioning
confidence: 52%
“…How alpha synuclein reaches serum from the brain in unknown, but blood levels of alpha synuclein may reflect the gene dosage and/or altered protein expression, since triplication of the alpha synuclein gene causes increased brain expression and a doubling of blood alpha synuclein (Miller et al, 2004). Cocaine abuse leads to state dependent increases in the levels of alpha synuclein in postmortem brain (Mash et al, 2003;Qin et al, 2005) and peripheral blood as shown in this report.…”
Section: Discussionmentioning
confidence: 52%
“…The size of the triplication region was over 2.0Mb. The expression values of messenger RNA and protein in peripheral blood and brain were twice the amount that is present in control subjects as predicted (Miller et al, 2004). Apart from the Iowan family, a www.intechopen.com Swedish-American family was also reported as a SNCA triplication family and the patients had DLB-type prognosis and pathological findings.…”
Section: Snca Triplication and Duplication In Hereditary Pdmentioning
confidence: 78%
“…Following this initial finding, Millter, et al found that the blood level of α-synuclein monomers was doubled in familial PD patients with α-synuclein gene locus triplication [8].…”
Section: The Finding Of Extracellular α-Synuleinmentioning
confidence: 90%